2011
DOI: 10.1007/s10198-011-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

Food prices and overweight patterns in Italy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…One plausible interpretation regards 13 Note that observations above 90% percentiles are sparse. See Pieroni et al (2011). the generally poor individual health condition of obese people, who are incentivated to stop smoking rather than to reduce cigarette consumption.…”
Section: Conditional Bmi Estimation: the Effects For Overweight And Omentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible interpretation regards 13 Note that observations above 90% percentiles are sparse. See Pieroni et al (2011). the generally poor individual health condition of obese people, who are incentivated to stop smoking rather than to reduce cigarette consumption.…”
Section: Conditional Bmi Estimation: the Effects For Overweight And Omentioning
confidence: 99%
“…Similar trends were observed for cigarette consumption (Colombo et al 2002). Conversely, body weight in Italy, expressed in terms of BMI, has increased consistently, although only in the last decade (Pieroni et al 2011). Using the ''Everyday Life Aspects" (ELA), a representative sample of microdata for Italy from 2001 to 2007, we can focus appropriately on this evidence and examine the magnitude of changes in smoking habits and BMI.…”
Section: Introductionmentioning
confidence: 99%
“…All specifications include province and district dummies, and also linear and quadratic trends to account for the non-linear patterns of food expenditure (Pieroni et al 2013;Pieroni and Salmasi 2015), together with the household and head of household characteristics (see Section 2). For each specification, we test for weak instruments.…”
Section: Results and Robustness Analysismentioning
confidence: 99%
“…The main shortcoming of the LP approach concerns the choice of the most appropriate bandwidth. We followCalonico et al (2014) for the best choice.13 As stressed byJacob et al (2012), more sophisticated functional forms may also be used as robustness checks of the linear formulation.14 We apply to food expenditure the procedure used byPieroni et al (2013) andPieroni and Salmasi (2015) to capture non-linear patterns in food consumption.…”
mentioning
confidence: 99%
“…Moreover, six studies28,29,31–34 and five studies35–39 examined the association between beverage/food prices and taxes and energy and weight outcomes, respectively. These studies indicated that there is a very small impact of prices and taxes on energy intake and weight outcomes.…”
Section: Resultsmentioning
confidence: 99%